054 The acceptability, feasibility and usability of the neotree application in malawi: an integrated m-health solution to improve quality of newborn care and survival in health facilities in resource-poor settings. (December 2018) - Heys, M; Crehan, C; Kesler, E; Nambiar, B; Dube, Q; Lufesi, N; Giaccone, M; Normand, C; Azad, K
Abstract : Background: More than two-thirds of newborn lives could be saved worldwide if evidence-based interventions were successfully implemented. We developed the NeoTree application to improve quality newborn care in resource-poor settings. It provides an integrated electronic platform for immediate digital data capture on admission, evidence-based clinical decision support, and newborn care education. Here, we tested the acceptability, feasibility and usability of the NeoTree prototype. Methods: This was a mixed method intervention development and acceptability, feasibility and usability study. Co-development and testing with healthcare workers (HCW) was conducted in a district hospital, Malawi. Focus groups explored the acceptability and feasibility of digital health solutions before and after implementation in the clinical setting. One-to-one theoretical usability workshops and a one-month clinical usability study gathered process and clinical data, systems usability scores (SUS) and qualitative data around usability and perceived improvements in quality of care. Results: Digital aids including the NeoTree were considered acceptable, feasible and a potential facilitator to quality newborn care (table 1). Identified factors predicted to aid the success of the NeoTree included positive staff attitude, training, strong leadership and staff engagement. Mean SUS before and after the clinical usability study was high at 80.4 and 86.1 respectively (above average is >68). HCWs reported high perceived improvements in quality of newborn care after using the NeoTree. They described improved confidence in clinical decision-making, clinical skills, critical thinking, and standardisation of care. Conclusion: The NeoTree is an agile, acceptable, feasible and highly usable tool with the potential to improve the quality of newborn care in resource-poor settings. Co-production, mixed methods approaches, and user-focused iterative development has been key to its success thus far. Next steps will focus on data linkage and evaluation within national systems.